Molecular docking analysis of curcumin analogues as human neutrophil elastase inhibitors - Narayanaswamy, Radhakrishnan; Lam, Kok Wai; Abas, Faridah; Ismail, Intan Safinar (Bangladesh Pharmacological Society, 2014)
In the present study, we aimed to dock 17 different ligands of curcumin analogues with that of human neutrophil elastase. Molecular descriptors analysis using Molinspiration online tool was carried out including investigation on human neutrophil elastase putative binding sites using Discovery Studio. The molecular physicochemical analysis revealed that all of the curcumin analogues complied well with the five rules of thumb. With regard to bioact-ivity score, compound 17 has exhibited least score towards nuclear receptor ligand (0.05) and enzyme inhibitor (0.10) compared to all other ligands. Compounds 2, 4 and 13 exhibited the maximum interaction energy (-40 kcal/mol). Interestingly, seven compounds namely 3, 11-14, 16 and 17 interacted well with Arg147 amino acid residue. The present study outcomes therefore might provide new insight in understanding these 17 curcumin analogues as potential candidates for human neutrophil elastase inhibitory agents.